Mitochondria Donation by Mesenchymal Stem Cells: Current Understanding and Mitochondria Transplantation Strategies - Gomzikova, Marina O.; James, Victoria; Rizvanov, Albert A. (Frontiers in Cell and Developmental Biology, 2021)
The phenomenon of mitochondria donation is found in various tissues of humans and animals and is attracting increasing attention. To date, numerous studies have described the transfer of mitochondria from stem cells to injured cells, leading to increased ATP production, restoration of mitochondria function and rescue of recipient cells from apoptosis. Mitochondria transplantation is considered as a novel therapeutic approach for the treatment of mitochondrial diseases and mitochondrial function deficiency. Mitochondrial dysfunction affects cells with high energy needs such as neural, skeletal muscles, heart and liver cells, and plays a crucial role in type 2 diabetes, as well as Parkinson's, Alzheimer's diseases, ischemia, stroke, cancer and age-related disorders. In this review, we summarize recent findings in the field of mitochondria donation and mechanism of mitochondria transfer between cells. We review the existing clinical trials and discuss advantages and disadvantages of mitochondrial transplantation strategies based on the injection of stem cells, isolated functional mitochondria or EVs containing mitochondria.